Management of arsenic trioxide necrosis in the maxilla - GARİP, HASAN (My University, 2004)
Historically, pulp-necrotizing agents were commonly used in endodontic treatments. They act quickly and devitalize the pulp within a few days. However, they are cytotoxic to gingiva and bone. If such an agent diffuses out of the cavity, it can readily cause widespread necrosis of gingiva and bone, which can lead to osteomyelitis of the jaws. Although the use of arsenic trioxide can cause severe damage to surrounding tissues, producing complications, it is still used in certain areas in the world. This article presents and discusses two cases of tissue necrosis and their surgical management. These cases showed severe alveolar bone loss in the maxilla, which affected the patients' quality of life and limited the restorative possibilities. As dentists, we should be aware of the hazardous effects of arsenic trioxide and should abandon its use. Because of its cytotoxicity, there is no justification for the use of arsenic trioxide in the modern dental practice.
Keywords: Adult; Female; Humans; Male; Alveolar Bone Loss; Oxides; Arsenicals; Arsenic Trioxide; Dental Pulp Devitalization; Osteonecrosis; Oroantral Fistula; Extravasation of Diagnostic and Therapeutic Materials; Maxillary Diseases